Enhanced Fuel Cell Performance of Decalin Treated Nafion® Membranes. Issue 1 (16th December 2014) - Krishnan, L.; Yeager, G.; Clark, K.; Kerr, J.; Soloveichik, G.
Abstract The interaction of Nafion® 212 membrane with a carbocyclic fuel, decalin was studied. Membrane electrode assemblies (MEA) fabricated with decalin treated membranes exhibited significant increase in power density in a H2/Air fuel cell at 60% relative humidity. Small angle X‐ray scattering experiments were used to understand the morphological changes in the membrane due to decalin treatment.